Search for heavy neutral leptons in W+ → μ+μ± jet decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (The European physical journal. C, Particles and fields, 2021)
A search is performed for heavy neutrinos in the decay of a W boson into two muons and a jet. The data set corresponds to an integrated luminosity of approximately $$3.0\, \text {fb} ^{-1} $$of proton-proton collision data at centre-of-mass energies of 7 and $$8\, \text {TeV} $$collected with the LHCb experiment. Both same-sign and opposite-sign muons in the final state are considered. Data are found to be consistent with the expected background. Upper limits on the coupling of a heavy neutrino with the Standard Model neutrino are set at $$95%$$confidence level in the heavy-neutrino mass range from 5 to $$50\, \text {GeV/}c^2 $$. These are of the order of $$10^{-3}$$for lepton-number-conserving decays and of the order of $$10^{-4}$$for lepton-number-violating heavy-neutrino decays.
Im Titel sind "±", und "+" hochgestellt
Gesehen am 04.05.2021